Crystal chemistry and ab initio DFT studies of original materials: superhard C5, C4N, and C2N2 nitrides - Samir F. Matar (Academia Materials Science)
Superhard C5 with lon topology (lon: Lonsdaleite hexagonal diamond), characterized by the presence of sp3 and sp-like carbon sites, is devised from crystal chemistry and used as a template matrix structure for identifying original carbonitrides C4N and C2N2, which also exhibit lon topology, except for the equiatomic belonging to a new topology (3,4L147). The steric effect of N(2s2) lone pair is highlighted in C2N2 through inducing an original structure with a largely separated two-layered stacking of tetrahedra. Such investigations, based on crystal chemistry rationale, were supported by computations within the framework of quantum density functional theory (DFT). All systems were found to be cohesive and both mechanically (elastic constants) and dynamically (phonon band structures) stable. Super hardness characterizes the carbon allotrope C5 and the nitrides C4N and C2N2. Metallic-like conductivities and insulating properties were identified, thus offering a range of materials for applications in the field of electronics.